Evidence for time-reversal symmetry-breaking kagome superconductivity - Deng, Hanbin (2025)
Superconductivity and magnetism are often antagonistic in quantum matter, although their intertwining has long been considered in frustrated-lattice systems. Here we utilize scanning tunnelling microscopy and muon spin resonance to demonstrate time-reversal symmetry-breaking superconductivity in kagome metal Cs(V, Ta)3Sb5, where the Cooper pairing exhibits magnetism and is modulated by it. In the magnetic channel, we observe spontaneous internal magnetism in a fully gapped superconducting state. Under the perturbation of inverse magnetic fields, we detect a time-reversal asymmetrical interference of Bogoliubov quasi-particles at a circular vector. At this vector, the pairing gap spontaneously modulates, which is distinct from pair density waves occurring at a point vector and consistent with the theoretical proposal of an unusual interference effect under time-reversal symmetry breaking. The correlation between internal magnetism, Bogoliubov quasi-particles and pairing modulation provides a chain of experimental indications for time-reversal symmetry-breaking kagome superconductivity.